Effects of different sowing time to phenology and yield of winter wheat - Klepeckas, Martynas; Januškaitienė, Irena; Vagusevičienė, Ilona; Juknys, Romualdas (Agricultural and Food Science, 2020)
This study aims to determine optimal sowing date for winter wheat (Triticum aestivum L.) and invoke DSSAT Nwheat model to analyze impact of modified sowing date to phenological development and grain yield. Wheat was grown for three seasons in two locations across Lithuania and sowing was carried out one time per week from 1 September to 29 September. Average three-year temperature of vegetation period gets lower every week by 0.16 °C, and available GDD by 94.5 °C when sowing time is delayed. Modeling results showed that tillering rate is affected by sowing time winter wheat grew 232 (tillers m-2) less with each week of delayed sowing. Grain filling stage was shortened by 1.25 days with each delayed sowing week. Depending on sowing time yield varied from 8.58 t ha-1 to 6 t ha-1 while simulated harvest was 8% lower. We conclude that best winter wheat sowing time for current climatic conditions in Lithuania is mid-September and DSSAT model proves as a useful tool in anticipating sowing time while facing problems caused by a climate change.